Money laundering in Decentralized Finance : Business Implications and Regulatory Challenges in Europe - Mesias Bolanos, Emiliano (2025)
This thesis explores the role of Blockchain Analytics in fighting money laundering within Decentralized Finance (DeFi) in the European Union. It shows how these tools help trace illicit transactions despite DeFi’s pseudonymity and decentralization. Case studies of Tornado Cash, Hydra Market, and ChipMixer demonstrate both the benefits and limitations of Blockchain Analytics in supporting AML enforcement in the EU.